Interaction of cigarette smoke condensate and some of its components with chlorpromazine toxicity on Saccharomyces cerevisiae. (2nd January 2022) - Sayyed, Katia; Aljebeai, Abdel-Karim; Al-Nachar, Mariam; Chamieh, Hala; Taha, Samir; Abdel-Razzak, Ziad
Abstract: Chlorpromazine (CPZ) is an antipsychotic phenothiazine which is still commonly prescribed though it causes idiosyncratic toxicity such as cholestasis. CPZ toxicity mechanisms involve oxidative stress among others. Cigarette smoke (CS) causes deleterious effects through diverse mechanisms such as oxidative stress. CS alters drug metabolizing enzymes expression and drug transporters expression and activity in animal cell models as well as in Saccharomyces cerevisiae . CS therefore alters pharmacokinetic and pharmacodynamics of many drugs including CPZ and caffeine whose toxicity is promoted by CS condensate (CSC). CSC interaction with CPZ toxicity deserves investigation. In this study, CSC exerted mild toxicity on Saccharomyces cerevisiae which resisted to this chemical stress after several hours. CPZ toxicity on yeast was dose-dependent and the cells resisted to CPZ up to 40 µM after 24 h of treatment. Yeast cells treated simultaneously with CPZ and a nontoxic CSC dose were less sensitive to CPZ. CSC probably triggers cross-resistance to CPZ. Using Sod1 mutant strain, we showed that this gene is potentially involved in the potential cross-resistance. Other genes encoding stress-related transcription factors could be involved in this process. Nicotine and cadmium chloride, which caused a dose-dependent toxicity individually, acted with CPZ in an additive or synergistic manner in terms of toxicity. Although our results cannot be extrapolated to humans, they clearly show that CSC and its components interact with CPZ toxicity.